2012
DOI: 10.1353/lit.2012.0044
|View full text |Cite
|
Sign up to set email alerts
|

Schema Criticism: Literature, Cognitive Science, and Social Change

Abstract: This article develops a new critical methodology, called schema criticism, for promoting social justice. Traditional methods of social criticism, including ideology critique and Foucauldian analysis, often fail to correct the faulty and harmful assessments of other people that underlie the punitive, violent, and counterproductive social policies, institutions, and structures that are dominant today. This is because such methods fail to alter certain deep cognitive structures that cognitive science has revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Such “empathetic crossings” can happen through reading and critical, collaborative reflection, she claims. Cognitive schema studies have shown that being introduced to “fictional exemplars” can shift people’s beliefs about real people in similar roles (Bracher, 2013). Protest novels “can engage readers in precisely the sorts of cognitive activities that have been found to correct faulty social information processing” (Bracher, 2013, p.17).…”
Section: Fiction Fandom and Peace Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Such “empathetic crossings” can happen through reading and critical, collaborative reflection, she claims. Cognitive schema studies have shown that being introduced to “fictional exemplars” can shift people’s beliefs about real people in similar roles (Bracher, 2013). Protest novels “can engage readers in precisely the sorts of cognitive activities that have been found to correct faulty social information processing” (Bracher, 2013, p.17).…”
Section: Fiction Fandom and Peace Educationmentioning
confidence: 99%
“…Cognitive schema studies have shown that being introduced to “fictional exemplars” can shift people’s beliefs about real people in similar roles (Bracher, 2013). Protest novels “can engage readers in precisely the sorts of cognitive activities that have been found to correct faulty social information processing” (Bracher, 2013, p.17). Bracher argues that such literature “constitutes radical cognitive politics, a mode of intervention that works to promote social justice by altering the cognitive roots of harmful and unjust social policies” (p. 31).…”
Section: Fiction Fandom and Peace Educationmentioning
confidence: 99%
“…Cristina Bruns posits that through collaboration and critical reflection, students are able to "produce the knowledge themselves through what they notice in one another's readings with the facilitation of the instructor, and they experience its value as a means of enriching their own encounters with the literary texts under discussion" (2011,137). In this way, students are able to make explicit connections between what they have learned about human rights vis-à-vis counter-narratives that correct their faulty cognitive schemas (Bracher 2013) regarding women's rights, social justice, and rights-based discourses promoted and controlled by Western nations.…”
Section: Critical Pedagogies In Action: Reflective Practice and Collamentioning
confidence: 99%
“…In a former issue of Radical Teacher, Nick Hengen Fox argues that "how we teach texts may matter more" than "what we teach in literature courses" (2012, 22, author's emphases). But what Fox fails to consider is the impact that literary counter-narratives have on shaping students' world-views, especially the way in which literature can reshape students' cognitive schemas (Bracher 2013). Kanishka Chowdhury posits that a literary text must be studied within "its sociocultural politics" (1992,192).…”
Section: Scaffolding For Skepticism: My Pedagogic Creedmentioning
confidence: 99%
See 1 more Smart Citation